Augmented Reality Trends in Teaching English Tenses: The Case of Non-English Education Students - Yelia Yelia; Dony Efriza; Santi Hendrayani (Universitas Jambi, Indonesia, 2021)
The purpose of this study was to examine a classroom action research about using augmented reality media to improve non-English students’ tenses mastery. The study was carried out in two cycles and each cycle consists of four stages, including plan, action, observation, and reflection. The participants of the study were a class of students of economic education study program, faculty of teacher training and education at a public university in Jambi who were taking English subject. The data of the study were taken from a test and observations in collecting the data. The results of the data analysis indicated that there was an increase from the first cycle to the second cycle. Moreover, the research results showed that: 1) augmented reality created a good atmosphere in the teaching and learning activities; 2) augmented reality made the students understand the use of tenses easily; and 3) the students became more active and attractive in the teaching and learning activities. It can be concluded that the use of augmented reality can improve students' tenses mastery.